TANGGUNGJAWAB PENYELENGGARA PEMBANGUNAN PERUMAHAN TERHADAP PENYERAHAN PRASARANA SARANA DAN UTILITAS UMUM DALAM PERUMAHAN KEPADA PEMERINTAH DAERAH (Lex Journal: Kajian Hukum & Keadilan, 2019)
Public Facilities and Public Utilities is one of the requirements that must be completed in developing a housing and residential areas. To ensure the sustainability of its maintenance and management so it can be utilized by resident community and urban community in general Developer must submit the Public Facilities and Public Utility they have built to the Regional Government, but it is often the Developer transfered the public Facilities to other parties instead of submitted to the Regional Governments which cause losses to the Regional Government. The intention of this study is to identify and analyze the responsibilities of a Housing Developers who already sell public fasility which should be transferred to the Regional Government and how the Regional Government should do to regain the public fasility in order to avoid any loses  of the government assets in terms of Regional Regulation Surabaya City number 7 of 2010 on Delivery of Infrastructure, Facilities and Public Utilities In Industrial Area, Trade, Housing and Settlement.Keywords: Infrastructure of Facilities and Utilities, Transferred, Responsibility